Assessment of Quality of Life and Psychological Distress in Chronic Suppurative Otitis Media Patients: A Cross-Sectional Study - Muhammad Saad Iqbal, Mishaal Zarar, Ayesha Shoaib, Sikander Hayat, Hamza Khan, Hussain Ahmed (Students' Supplement of Journal of Rawalpindi Medical College, 2025)
Background: Chronic Suppurative Otitis Media (CSOM) is a debilitating middle ear condition associated with hearing loss and persistent ear discharge. While its physical aspects have been thoroughly investigated, the psychological impact it produces on the patients remains widely unexplored in developing countries like Pakistan. This study aims to evaluate the link between CSOM and psychological distress using the DASS-21 scale, and also the Quality of Life (QoL) in patients using the Chronic Ear Survey (CES). Methodology: A cross-sectional descriptive study was carried out in Fauji Foundation Hospital, Islamabad, from February to July 2025. A total of 110 patients who were clinically diagnosed with Chronic Suppurative Otitis Media (CSOM) were recruited using a non-probability convenience sampling technique, and written informed consent was obtained from them. Those with a history of severe psychiatric conditions, acute otitis media, or serious comorbid medical conditions were not included. Data was collected using the Depression Anxiety Stress Scales (DASS-21) and CES scales. Data was analyzed using SPSS version 26 with descriptive and inferential statistics. Results: Most of the patients, out of 110, have had CSOM for over 10 years (62%) and suffered mild to moderate symptoms. Signs of psychological distress were more common in females and those with prolonged illness. A significant association was found between prolonged ailment and depression (r =.354), stress (r =.376), and anxiety (r =.317). Females exhibited higher scores in DASS-21 and CES scales than males, which heavily impacted QoL in these patients. Conclusion: In conclusion, Chronic Suppurative Otitis Media (CSOM) significantly impacts the psychological health and quality of life (QoL) of its victims, particularly females and long-term sufferers. The results highlight the importance of a multidisciplinary approach that includes psychological support alongside medical treatment to reduce psychological distress and improve the physical well-being of the patients. The study was conducted at a single tertiary care hospital (Fauji Foundation Hospital), which may limit the generalizability of the findings. Key Words: Chronic suppurative otitis media, Quality of life, Psychological distress